Physical characterization and durability of blended cements based on brick powder - Nigri, Ghania; Cherait, Yacine; Nigri, Soraya (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This research work discusses both the physical and durability characteristics of newly blended cement containing waste crushed brick. This waste is used as a partial substitution for clinker in cement. Thus, blended cements are obtained by grinding and homogenizing clinker, waste brick, and gypsum. Four compositions containing 0%, 10%, 20%, and 30% of waste materials were prepared and submitted to various characterization tests. The introduction of brick powder improved the physical characteristics, therefore; it improved the mechanical properties and durability performance of the new cement compared to the reference, prepared with 0% addition. More particularly, it resisted sulfuric acid (H2SO4) attack after fixation of portlandite by pozzolan.
Keywords: waste brick; blended cement; durability; capillarity; porosity; X-ray diffraction; pozzolanic reaction; cegła; cement mieszany; trwałość; porowatość; kapilarność; dyfrakcja rentgenowska